2017
DOI: 10.1186/s12884-017-1448-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing implementation of interventions to promote birth preparedness and complication readiness

Abstract: BackgroundThe recent WHO report on health promotion interventions for maternal and newborn health recommends birth preparedness and complications readiness interventions to increase the use of skilled care at birth and to increase timely use of facility care for obstetric and newborn complications. However, these interventions are complex and relate strongly to the context in which they are implemented. In this article we explore factors to consider when implementing these interventions.MethodsThis paper repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
1
20
0
7
Order By: Relevance
“…The autonomy of the mother and the decision-making process has a significant contribution in reaching care on time. A study reports that the process is influenced by various other factors such as women education, belief system of family, resource scarcities and financial constraints [20].…”
Section: Discussionmentioning
confidence: 99%
“…The autonomy of the mother and the decision-making process has a significant contribution in reaching care on time. A study reports that the process is influenced by various other factors such as women education, belief system of family, resource scarcities and financial constraints [20].…”
Section: Discussionmentioning
confidence: 99%
“…While it has been estimated and studied in previous research in Ethiopian context [26], limited number of articles were included in the former article [26] and did not address factors affecting for low utilization of BPCR. However, there was a narrative synthesis of qualitative information on implementation of BPCR [27]. But in the motioned study [27] review the existing article using narrative review, which was prone selection and evaluation bias and even not reproducible.…”
Section: Introductionmentioning
confidence: 99%
“…The overall nding of this study showed a huge gap in the utilization of BP/CR by male partners of pregnant women and nursing mothers in low-and middle-income countries. This indicates the higher maternal and neonatal mortality in the global south could be attributed to the underutilization of birth preparedness and complication readiness packages by male partners, as lack of funds for the birth of the child and emergency case during the delivery and postpartum period coupled with being poorly prepared to identify potential blood donor for probable emergency largely delays access to emergency obstetrics and newborn care (EmONC) in event of complication [60][61][62]. Therefore, policymakers and program planners should make targeted intervention by reviewing maternal and neonatal healthcare delivery guidelines to include context-speci c evidence and develop evidence-informing interventions promoting male partner's active involvement in birth preparedness and complication readiness [63,64].…”
Section: Discussionmentioning
confidence: 99%